Calf circumference to detect low birth weight babies: a comparative study - Kokku, Pradheep Kumar; Singh, Himabindu; Kotha, Rakesh; Jadhavo, Arjun; Maddireddi, Alimelu; Cherukuri, Nirmala; Anjum, Sadiqua; Tadury, Apoorva (International Journal of Contemporary Pediatrics, 2019)
Background: In developing countries 15 per cent of infants weigh less than 2,500 grams at birth .It is not possible to provide expensive weighing scales to the community members and families due to logistic (carrying a heavy scale) and operational (inability of Trained Birth Attenders to read) problems. Therefore it is essential to find out an alternative method for the estimation of birth weight. Almost 60 per cent of newborns in developing countries are not weighed. Which can lead to an underestimation of the incidence of low birth weight. That’s why we done present study to know the simple indicators to detect low birth weight babies. Aim of this study to compare calf circumference with other Low birth weight indicators as a reliable predictor of low birth weight babies. Methods: It is a cross-sectional study done during period 2018 January to 2018 October done at Niloufer Hospital Hyderabad. Statistical analysis is done using SPSS (version 17) statistical software. For comparison Pearson's Correlation coefficients used. Results: The best correlation was observed with both calf circumference (r=0.818) and head circumference (r=0.744) for identifying babies with birth weight <2 kg. For babies with birth weight <2.5 kg, calf circumference had the highest order of correlation (r = 0.986) followed closely by head circumference (r=0.886). Conclusion: In the absence of a weighing machine, simple measurements like calf circumference is the best indicator in identifying low birth weight babies (<2.5kg) at birth.